2008
DOI: 10.1063/1.3037224
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced fluorescence from Eu3+ in low-loss silica glass-ceramic waveguides with high SnO2 content

Abstract: We report on the sol-gel fabrication and characterization of (100−x)SiO2–xSnO2 (x=8, 16, and 25mol%) glass-ceramic waveguides doped with 1mol% Eu3+. A suitable top-down thermal process led to the formation of SnO2 nanocrystals ∼4nm embedding Eu3+ ions. The excitation spectra evidence the role of interband electronic transition of SnO2 nanocrystals on the luminescence of Eu3+. Monitoring the D05→F27 Eu3+ emission, we observe about 15 times increase in the intensity of SnO2 absorption band, moving from x=8to25mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 22 publications
3
35
0
Order By: Relevance
“…Figure 6 shows the 1.5 μm photoluminescence spectra of 30SnO 2 -70SiO 2 glass-ceramic thin films doped with different concentration of Er 3+ ranging from 1 up to 3 mol% upon excitation at 300 nm. The luminescence spectra indicates an efficient energy transfer from the SnO 2 nanocrystals to the rare earth ions [5]. Moreover, the narrowing of the emission peaks, associated to the Stark multiplets, evidences that the rare earth ions are embedded in the SnO 2 nanocrystals.…”
Section: Transparencymentioning
confidence: 92%
See 1 more Smart Citation
“…Figure 6 shows the 1.5 μm photoluminescence spectra of 30SnO 2 -70SiO 2 glass-ceramic thin films doped with different concentration of Er 3+ ranging from 1 up to 3 mol% upon excitation at 300 nm. The luminescence spectra indicates an efficient energy transfer from the SnO 2 nanocrystals to the rare earth ions [5]. Moreover, the narrowing of the emission peaks, associated to the Stark multiplets, evidences that the rare earth ions are embedded in the SnO 2 nanocrystals.…”
Section: Transparencymentioning
confidence: 92%
“…In [4], undoped thin films were fabricated with different molar percentages of SnO 2 : from 12 mol% to 60 mol% in order to focus on the compositional effects. In this case, the limit of SnO 2 concentration embedded in host material reached 30 mol% instead of 25 mol% like in earlier approaches [5] [6]. Van et al [7] recently suggested that Er 3+ inhibits the growth of SnO2 crystals on the surface of SiO 2 -SnO 2 films, so the effect of rare earth on the SnO 2 crystallization deserves careful investigation.…”
Section: Introductionmentioning
confidence: 97%
“…Now, this expectation is a reality, as demonstrated by several glass-ceramicbased systems reported in literature where the common goal is the waveguiding property [28,13]. From a general point of view it is evident that RED integrated optical amplifiers and laser systems exhibit chemical and physical effects, mainly linked to the ion-ion interactions as well as to the nonradiative relaxation processes, which are detrimental for the efficiency of active waveguide and have been the subject of several scientific and technological investigations [2].…”
Section: Rare Earth-doped Transparent Glass Ceramicsmentioning
confidence: 93%
“…In fact, the embedded rare-earth-doped nanocrystals with low cutoff vibrational energy, such as hafnia, fluoride, titania, tin oxide, and zirconia, reduce the nonradiative contribution to the relaxation mechanism, allowing high fluorescence efficiency. Finally, some kind of nanocrystals such as SnO 2 have demonstrated to be excellent rare earth sensitizers and excellent SiO 2 -SnO 2 waveguides have been demonstrated [12][13][14]. We want close this section about glass-ceramics pointing out the advantage of this system for energy transfer optimization.…”
Section: Rare Earth-doped Transparent Glass Ceramicsmentioning
confidence: 99%
See 1 more Smart Citation